Marketing Communication on Food Processed (MSME) In Pontianak City - Sapitri, Sapitri; Kurniati, Dewi; Oktoriana, Shenny (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020DO - 10.24843/SOCA.2020.v14.i02.p03, 2020)
The selection of the marketing communication domain plays a major role in promoting products and services. The most common problem in Micro, Small, and Medium Enterprises (MSME) is its funding system. This study aimed to know the integrated communication marketing used in food processing MSME in Pontianak City. This study was involving 100 participants chosen based on the purposive sampling technique. The analysis method used was descriptive and qualitative analysis. Through a descriptive analysis, the variable studied was described. While, the qualitative analysis applied in assessing the data sources, data reduction, and deducting conclusions or verifications. The result showed that integrated communication marketing that consisted of media advertising, sales promotion, and direct marketing are highly contributed to the food processed sales performance in Pontianak City.